(untitled) (Biodiversitas Journal of Biological Diversity, 2006)
This study analysed the response of dung beetles − a group of beetles which play a major role in decomposition of dung and animal carcasses − to changes of vegetation structure due to forest conversion to different human-made habitat types at the margin of Lore Lindu National Park. Therefore, dung beetles were sampled at natural forest, cacao agroforestry systems and open area. A total of 28 species of coprophagus beetle species were recorded from the sampled sites. Species richness and abundance of dung beetles, particularly of large species, decreased from forest towards agroforestry systems and open areas. However, more than 80 % of the species recorded in natural forest were found in cacao agroforestry systems Of the measured habitat parameters, particularly the number of tree species, air temperature, and canopy cover had a significant power for explaining changes in dung beetle ensembles along the gradient of land-use intensity. © 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: Coprophagus beetles, forest conversion, vegetation structure, cacao agroforestry